STRATEGI PENGEMBANGAN PENDIDIKAN ANAK USIA DINI (Perspektif Dakwah Nabi) - Isya Siti Aisyatul Mahmudah Badruzaman; Sopaat Rahmat Slamet (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2020)
Early Childhood Education has grown in our society. But on the other hand, the problem of violence against children (KDRT), including early childhood, is still an important issue in this country. This is because parents' understanding of the meaning of education as a whole, let alone exemplified by the Prophet, is apparently still uneven. Even though the principles of early childhood education in the prophet's perspective already exist and can be role models. So, the objectives of this study are (1) to arouse awareness of parents to imitate the Prophet in early education for children, (2) to find a character education development strategy in early childhood education by involving parents This research method uses a qualitative research approach with text analysis (discourse), an objective hermeneutic approach to verses and hadiths as well as sources of information. The theory used in this study is the concept of AUD and combines the basic principles of verses from the Qur'an and Hadith and narrations. . The results of this study indicate that (1) at least 10 points of early childhood education have been exemplified by the Prophet in various aspects of children's life, in worship practices, and morals (2) strategies for developing early childhood education with the perspective of the Prophet's da'wah can be done by: strengthening communication parents with teachers, strengthening parent human resources with parenting study material, and strengthening the relationship between parents and teachers through family gathering activities.Keywords: da'wah, domestic violence, early childhood education, education, early childhood, Abstrak Pendidikan Anak Usia Dini sudah tumbuh di masyarakat kita. Tetapi pada sisi lain problem kekerasan terhadap anak-anak (KDRT), termasuk anak usia dini masih menjadi persoalan penting di negeri ini. Hal ini karena pemahaman orangtua terhadap makna pendidikan secara utuh apalagi diteladankan Nabi saw tampaknya masih belum merata. Padahal prinsip pendidikan anak usia dini dalam perspektif nabi sudah ada dan bisa jadi teladan. Maka, tujuan penelitian ini adalah (1) untuk menggugah kesadaran orangtua untuk meneladani Nabi saw dalam pendidikan sejak dini bagi anak-anak, (2) menemukan strategi pengembangan pendidikan karakter pada anak PAUD dengan melibatkan orangtua murid. Metode penelitian ini menggunakan pendekatan riset kualitatif dengan analisys text (wacana) pendekatan metode hermeneutic obyektif atasayat-ayat dan hadis serta sumber informasi.Teori yang digunakan dalam penelitian ini konsep AUD dan menggabungkan dengan prinsip dasar ayat Al-Qur’an dan Hadits serta riwayat. Hasil Penelitian ini menunjukan bahwa (1) setidaknya ada 10 poin pendidikan anak sejak dini telah dicontohkan Nabi saw dalam berbagai aspek kehidupan anak, dalam praktek ibadah, dan akhlak (2) strategi pengembangan PAUD dengan perspektif dakwah nabi saw bisa dilakukan dengan cara: penguatan komunikasi orangtua dengan guru, penguatan SDM orangtua dengan materi kajian parenting, dan penguatan silaturahmi orangtua dengan guru melalui kegiatan Family gathering.Kata kunci: dakwah, KDRT, PAUD, pendidikan, usia dini